CB-1 receptor agonist drastically changes oscillatory activity, defining active sleep - Irina Topchiy; Bernat Kocsis (Proceedings of the National Academy of Sciences, 2025)
Brain oscillations in different behavioral states are essential for cognition, and oscillopathies contribute to cognitive dysfunction in neuropsychiatric diseases. Cannabis-1 receptor (CB1-R) activation was reported to suppress theta and fast gamma activities in rats during waking exploration, and here, we show that cannabis fundamentally alters network activity during sleep as well. Prominent theta rhythm is present in rapid eye movement sleep (REMS), whereas fast oscillations appear as regular sequences of sleep spindles during intermediate sleep (IS)—both implicated in dreaming and memory consolidation. The CB1-R agonist disrupted these mechanisms, restructuring IS-REMS episodes; IS lengthened sixfold and intruded REMS, where ongoing theta was drastically reduced. The spindle architecture was also affected; its amplitude increased, and its peak frequency downshifted into the theta range. Cannabis is known to induce psychotic-like conditions and cognitive deficits; thus, our results may help in understanding the dual effect of cannabis on cognitive states and the role of network oscillations in psychiatric pathology.